Sugar content and erosive potential of commonly prescribed Orodispersible tablets- An in vitro study. [version 1; peer review: 2 approved] - Saurabh Kumar; Kalyana Pentapati; Revathi Shenoy; Geethika Yelleti; Lahari Anand (F1000Research, 2023)
Background: Dental caries is a major non-communicable disease of public health concern caused due to freely available dietary sugars. We aimed to compare the sugar content and erosive potential with duration of use and drug classes of orodispersible tablets (ODTs).  Methods: We conducted an in vitro evaluation of the total sugar content (TSC), Potential of Hydrogen (pH), solubility, and Titratable Acidity (TA) of commonly prescribed 62 ODTs. TA was measured by titrating the samples with known amount of. 0.1N sodium hydroxide (NaOH) with phenolphthalein indicator and pH was determined by digital pH meter. TSC was evaluated by phenol sulphuric acid. Solubility was assessed by filtration.  Results: Out of the 62 ODTs, majority were Antimicrobials (n=30). One-quarter of the ODTs (26%) had a mean pH below ≤5.5. No significant difference was seen in the mean pH with respect to different drug classes (p=0.082) and duration of use of ODTs. A significant difference was seen in the mean percentage solubility with respect to drug classes (p<0.001). Antimicrobials had the least percentage of solubility as compared to other drug classes. Antiemetics and proton pump inhibitors (24.33 ± 17.34) had significantly higher mean percentage sugar content than Antimicrobials (23.25 ± 17.16). No significant difference was seen in the mean TSC with respect to various drug classes (p=0.718) and between the duration of use of drugs (P=0.568) respectively. No significant difference was seen in the mean percentage TA with respect to drug class (p=0.123) and duration of use of drugs (p=0.424).  Conclusion: Overall, we can conclude that one in four ODT formulations had a pH below 5.5 (critical pH).  Only one ODT formulation did not have a sugar content. No difference was seen in the mean pH, sugar content, and TA with respect to duration of use of drugs and drug classes.